Surgical Site Infection: Still Waiting on the Revolution - ANTHONY, Thomas; MURRAY, Bryce W; SUM-PING, John T; LENKOVSKY, Fima; VORNIK, Vadim D; PARKER, Betty J; MCFARLIN, Jackie E; HARTLESS, Kathleen; HUERTA, Sergio (JAMA : the journal of the American Medical Association, 2011)
Anthony et al determine if an evidenced-based practice bundle would result in a significantly lower rate of surgical site infections (SSIs) when compared with standard practice. The overall rate of SSI was 45% in the extended arm of the study and 24% in the standard arm (P=.003). Most of the increased number of infections in the extended arm were superficial incisional SSIs (36% extended arm vs 19% standard arm; P=.004). Multivariate analysis suggested that allocation to the extended arm of the trial conferred a 2.49-fold risk (95% confidence interval, 1.36-4.56; P=.003) independent of other factors traditionally associated with SSI. An evidenced-based intervention bundle did not reduce SSIs. The bundling of interventions, even when the constituent interventions have been individually tested, does not have a predictable effect on outcome. Formal testing of bundled approaches should occur prior to implementation.